The Financial Decisions of Immigrant and Native Households: Evidence from Italy - Graziella Bertocchi; Marianna Brunetti; Anzelika Zaiceva (Global Labor Organization (GLO), 2018)
Using rich Italian data for the period 2006-2014, we document sizeable gaps between native and immigrant households with respect to wealth holdings and financial decisions. Immigrant household heads hold less net wealth than native, but only above the median of the wealth distribution, with housing as the main driver. Immigrant status reduces the likelihood of holding risky assets, housing, mortgages, businesses, and valuables, while it increases the likelihood of financial fragility. Years since migration, countries of origin, and the pattern of intermarriage also matter. The Great Recession has worsened the condition of immigrants in terms of wealth holdings, home ownership, and financial fragility.
Keywords: F22; G11; D14; E21; J15; 330; immigrants; household finance; wealth; financial portfolios; Great Recession